Hybrid controller strategy for optimization of cumulated thermal stresses, induced in X-rays tube for medical use - Rachedi Mohamed; Bouanane Abdelkrim (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This work presents a new control strategy of the power supply, in favor of equipment intended for the medical use. Several research investigations have been reserved for the service of this supply type, but there are still some disadvantages, which have challenged their high performance in the practical side, in particular the problems which concern the weight, the size and especially, the efficiency of these installations and this, on the cost side, energy balance, and lifetime of this equipment. A control technique is presented to overcome these constraints; its principle is based on the deduction of a hybrid control of which two controllers are simultaneously used for the same radiological dose, known by the fuzzy logic and the PID which have already been tested [1], [3]. This hybrid control has been greatly enhanced and developed, thanks to its robustness against the various intolerable dynamic states applied to the system and also to the unpredictable external disturbances.